Closely Reading Informational Texts in the Primary Grades. (1st October 2014) - Fisher, Douglas; Frey, Nancy
Abstract In this article we discuss the differences between close reading in the primary grades and upper elementary grades. We focus on text selection, initial reading. repeated reading, annotation, text‐based discussions, and responding to texts.